Flexible microresonators : lasing and sensing - Ta, Van Duong (2014)
Microresonators have drawn a great deal of interest for their importance in both practical applications and fundamental physics in light-matter interaction. The optical confinement provided by a microresonator greatly enhances the interaction between optical spatial mode and the light emitting materials. Conventional fabrication of microresonators adopting semiconductor processing technology (no matter top-down or bottom-up approach) still faces some challenges. Here we report the feasibility of constructing solid state microresonators with various configurations including spheres, hemispheres and fibres from organic polymer in a flexible way. We realize optically pumped lasing from these structures after incorporating organic dye materials and/or colloidal quantum dots into the resonators. The lasing characteristics have been systematically examined in terms of size dependence and polarization. The longitudinal optical modes are well defined by whispering gallery modes. We are also able to tune the resonance modes by deforming the shape of micro-spheres, representing the facile manipulation of light-matter interaction. Finally, refractive index sensing with high sensitivity can be readily realized from these structures enabled by the existence of evanescent waves and improved by Vernier effect in coupled resonators.